Whole-body fat oxidation increases more by prior exercise than overnight fasting in elite endurance athletes - Andersson Hall, U.; Edin, F.; Pedersen, A.; Madsen, K. (Applied Physiology, Nutrition, and Metabolism, 2016)
The purpose of this study was to compare whole-body fat oxidation kinetics after prior exercise with overnight fasting in elite endurance athletes. Thirteen highly trained athletes (9 men and 4 women; maximal oxygen uptake: 66 ± 1 mL/min·kg) performed 3 identical submaximal incremental tests on a cycle ergometer using a cross-over design. A control test (CON) was performed 3 h after a standardized breakfast, a fasting test (FAST) 12 h after a standardized evening meal, and a postexercise test (EXER) after standardized breakfast, endurance exercise, and 2 h fasting recovery. The test consisted of 3 min each at 30%, 40%, 50%, 60%, 70%, and 80% of maximal oxygen uptake and fat oxidation rates were measured through indirect calorimetry. During CON, maximal fat oxidation rate was 0.51 ± 0.04 g/min compared with 0.69 ± 0.04 g/min in FAST (P < 0.01), and 0.89 ± 0.05 g/min in EXER (P < 0.01). Across all intensities, EXER was significantly higher than FAST and FAST was higher than CON (P < 0.01). Blood insulin levels were lower and free fatty acid and cortisol levels were higher at the start of EXER compared with CON and FAST (P < 0.05). Plasma nuclear magnetic resonance-metabolomics showed similar changes in both EXER and FAST, including increased levels of fatty acids and succinate. In conclusion, prior exercise significantly increases whole-body fat oxidation during submaximal exercise compared with overnight fasting. Already high rates of maximal fat oxidation in elite endurance athletes were increased by approximately 75% after prior exercise and fasting recovery.